Analysis of Village Fund Management in Village Development Efforts in Giri Mukti Village, Penajam District, Penajam Paser Utara Regency - Camelia Verahastuti; Zilfana; Dimas Chandra Surya Bimantara (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
Analysis of Village Fund Management in Village Development Efforts in Giri Mukti Village, Penajam District, North Penajam Paser Regency under the guidance of Mrs. Camelia Verahastuti as Supervisor I and Mrs. Zilfana as Supervisor II. The government hopes that the allocation of village funds can enhance rural development and welfare by improving public services, advancing the economy, and reducing disparities between villages. However, the potential for errors in village fund management must be guarded against from planning to reporting. Therefore, the implementation of transparency, accountability, and community participation in financial management and governance performance of the village is crucial. Based on the background and problem formulation outlined, the objective of this study is to investigate and analyze how the management of village funds can enhance rural development in Giri Mukti Village, Penajam District, Penajam Paser Utara Regency. This research utilizes a qualitative descriptive-comparative approach, involving the comparison of field facts with the provisions in the Ministry of Home Affairs Regulation Number 20 of 2018 concerning Village Financial Management. Researchers employ observation, interviews, and documentation as data collection instruments. The analysis is conducted qualitatively by presenting data and drawing conclusions. The research findings indicate that Giri Mukti Village has adhered to the principles of transparency, accountability, participation, orderliness, and discipline in managing the use of village funds, while also considering all stages of village financial management, namely planning, implementation, bookkeeping, reporting, and accountability.